PENGEMBANGAN PAKET PEMBELAJARAN ILMU PENGETAHUAN SOSIAL KELAS IV SD - Muhammad Lukman Syafii (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2017)
The textbook is designed to serve the basic principles or aspects containing in the medium of instruction. At SDN Kwagean II Loceret Nganjuk, the textbook becomes the most dominant medium in the instructional process. Another problem in the utilization of the textbook, the textbook has not met the feasibility aspect due to the theory, model, students’ need and the improvement of the students’ motivation. Therefore, the developer aims at developing a product of Social Science (IPS) instructional package for IV graders of Elementary School to solve the existing problem concerning the textbook at SDN Kwagean II Loceret Nganjuk. Regarding the problems, the developer considers the importance for reorganizing the social science material for the fourth graders of elementary school by designing, trying out and producing it in the form of complete instructional package. The conclusion of the field test done after going through expert analysis, individual and small group tests can be said that the textbook has fulfilled the students’ need even though there are some matters to be revised. It is expected that IPS Textbook for IV graders is able to solve the problems concerning the instructional package development that comply with the theory and learning model, so it can generate a learning source that is proper with the students’ characteristics, assist the students’ learning and create such learning condition that may improve the students’ motivation.